PROSPECTS FOR USING SPIRITUAL POTENTIAL IN BUILDING A NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article, the author describes the role of the reforms implemented in New Uzbekistan in social development, highlights thoughts on transforming the country into a comprehensively prosperous country with strong potential and a worthy reputation on the world stage, and also argues that the new Development Strategy of Uzbekistan represents a holistic moral a basis that unites our people for common goals.